1992
DOI: 10.1126/science.1312256
|View full text |Cite
|
Sign up to set email alerts
|

The fms -Like Tyrosine Kinase, a Receptor for Vascular Endothelial Growth Factor

Abstract: The fms-like tyrosine kinase (Flt) is a transmembrane receptor in the tyrosine kinase family. Expression of flt complementary DNA in COS cells conferred specific, high-affinity binding of vascular endothelial growth factor, also known as vascular permeability factor (VEGF-VPF), a factor that induces vascular permeability when injected in the guinea pig skin and stimulates endothelial cell proliferation. Expression of Flt in Xenopus laevis oocytes caused the oocytes to release calcium in response to VEGF-VPF. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
967
1
23

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,879 publications
(999 citation statements)
references
References 25 publications
8
967
1
23
Order By: Relevance
“…VEGF has been shown to be a specific endothelial cell mitogen in vitro (Gospodarowicz et al, 1989). Two high-affinity VEGF receptors (flt-I and KDR) have been recognized on human endothelial cells (de Vries et al, 1992;Terman et al, 1992). The expression of VEGF is correlated to vascular density in several histological types of human tumours (Guidi et al, 1995;Takahashi et al, 1995;Toi et al, 1995;Mattern et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has been shown to be a specific endothelial cell mitogen in vitro (Gospodarowicz et al, 1989). Two high-affinity VEGF receptors (flt-I and KDR) have been recognized on human endothelial cells (de Vries et al, 1992;Terman et al, 1992). The expression of VEGF is correlated to vascular density in several histological types of human tumours (Guidi et al, 1995;Takahashi et al, 1995;Toi et al, 1995;Mattern et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…8 Another high-affinity VEGFR, Flt-1, binds VEGF about 10 times stronger than KDR, however Flt-1 activation does not significantly stimulate angiogenesis. 9,10 Both receptors, Flt-1 and KDR, have similar structure with extracellular regions consisting of seven domains, 1-7. 10,11 There exists another naturally occurring soluble form of Flt-1 (sFlt-1) that contains only the extracellular domains and has the same VEGF-binding affinity as full-length Flt-1.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 VEGF binds to two highly specific tyrosine kinase receptors, Flt-1 and KDR/Flk-1, found almost exclusively on endothelial cells. [34][35][36] Following receptor binding, endothelial cells are stimulated to proliferate and form tube-like structures, the first steps in forming new blood vessels, a process known as angiogenesis. 37,38 Preclinical studies have demonstrated that delivery of the VEGF gene into ischemic tissue can stimulate the development of collateral arteries in animal models of peripheral and myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%